University Social Responsibility and Interculturality Among Students at a Professional School in Peru (Docentes 2.0 Journal, 2025)
At an intercultural university, social responsibility must be embedded in Interculturality to achieve cultural diversity and preserve the ancestral knowledge of native communities. The purpose of this research was to determine the relationship between university social responsibility (USR) and Interculturality among students at the Professional School of Environmental Engineering, Pichanaqui, 2024. The research was conducted within the positivist paradigm, employing a hypothetical-deductive method, a quantitative approach, and a non-experimental, correlational, cross-sectional design. The sample consisted of 234 students who participated in the questionnaires. The validation was carried out through the judgment of three experts reflecting validity and good agreement and reliability by Cronbach's Alpha (RSU = 0.905 and Interculturality = 0.856) which represented very good reliability, referring to the normality of the data, Kolmogorov-Smirnov was used (p = 0.00 < p = 0.05) indicating that the data do not present a normal distribution and to determine the correlation Spearman's Rho was used. The results indicate a very weak, direct, and significant (positive) relationship between RSU and Interculturality (Spearman's Rho = 0.083). It is concluded that the university must implement and execute activities that help students comply with RSU, thereby improving the relationship with Interculturality.
Keywords: Native community; cultural diversity; indigenous peoples; society; university